GlyT1 inhibitor reduces oscillatory potentials of the electroretinogram in rats. (September 2014) - Liu, Chang-Ning; Pettersen, Betty; Seitis, Gary; Osgood, Sarah; Somps, Chris
Abstract Context: Selective inhibitors of glycine transporter type 1 (GlyT1) increase synaptic glycine concentrations and are being developed to treat cognitive and negative symptoms of schizophrenia. However, increases in systemic glycine levels have been associated with visual disturbances and electroretinogram (ERG) alternations. Objective: To determine whether the selective GlyT1 inhibitor PF-03463275 causes changes in ERG responses in albino rats. Materials and methods: Male Sprague-Dawley rats were administered PF-03463275 subcutaneously at 1, 3 and 10 mg/kg 1 h prior to ERG acquisition. Scotopic and photopic luminance responses, photopic adaptometry and flicker responses were measured. Plasma and vitreous samples were obtained at necropsy for determination of PF-03463275 concentrations. Results: A dose-dependent reduction (up to ∼70%) in the amplitude of the scotopic ERG oscillatory potentials (OPs) was observed following PF-03463275 administration. The amplitude of the OPs was also negatively correlated to the concentration of PF-03463275 in the vitreous humor (r = −0.64, p < 0.0001). With the exception of a small increase in scotopic ERG a-wave amplitude and latency no effects were observed on other ERG parameters tested. Conclusions: We conclude that inhibition of the GlyT1 transporter in the retina causes ERG changes which may underlie recent reports of visual disturbance with GlyT1 inhibitors in clinical trials.